Fetal Anomalies in Ultrasonographically Detected Polyhydramnios - Asad Iqbal Mughal, Muhammad Ashraf, Syed Atif HussainAndrabi,Atif Latif,Memoona Chiragh (Journal of Rawalpindi Medical College, 2010)
Background: To determine the frequency and types of fetal anomalies in cases of polyhydramnios detected on ultrasonography and to compare maternal age and parity of these subjects with fetal anomalies and those without fetal anomalies. Methods: In this cross sectional study, using colour and power Doppler ultrasound machine, one hundred diagnosed patients with ultrasonographically detected polyhydramnios were included . Sonographic examination was conducted between 12 to 40 weeks of gestation and fetal anomalies were examined. Results: Out of 100 patients, 35 fetal anomalies were found in 30(30%) patients. The age of the patients included in the study ranged from 18 to 40 years. Majority of the anomalies (73%) were found between age group 30 – 40 years and in multigravida (83%). Central Nervous System was the commonest site with fetal anomalies (46%) followed by gastrointestinal tract (20%) Conclusion: Prenatal detection of fetal anomalies has a decisive effect on the outcome of pregnancy and helps the obstetrician in planning the intrapartum management and for post delivery resuscitative measures, if required